Ketahanan Energi di Daerah Terpencil: Studi Tekno-Ekonomi Sistem Tenaga Surya Off-Grid pada Kondisi Iklim Mikro Dataran Tinggi - Misbahul Munir, Misbahul Munir; Moch. Septian Dwi Rohmat Ari Wibowo, Moch. Septian Dwi Rohmat Ari Wibowo; Moh. Anton Rahmawijaya, Moh. Anton Rahmawijaya; Muhammad Alfarid Zidan, Muhammad Alfarid Zidan; Noval Isa Mahendra, Noval Isa Mahendra (Politeknik Caltex Riau, 2025)
In Indonesia's poor, frontier, and remote areas, access to power is still hampered by a lack of network infrastructure and high transportation costs for fossil fuel supply. The techno-economic viability of an off-grid solar power system without a generator set in the vicinity of Nduga Regency is examined in this paper. HOMER Pro software was used for modeling. Local solar radiation potential, daily electricity consumption profiles, battery characteristics, and estimates about maintenance and investment costs were among the input data. The research concentrated on dependability metrics like Loss of Load Probability (LOLP) and indicators like Levelized Cost of Energy (LCOE), Net Present Cost (NPC), and Internal Rate of Return (IRR) in order to identify the best battery SPP configuration. According to simulation studies, solar systems with battery-based energy storage are both economically competitive during the project time and can supply off-grid populations with dependable electricity. However, this design necessitates a substantial initial expenditure due to logistical and topographical challenges. Using off-grid solar power plants without generators is a promising way to increase electrification, improve energy security, and lessen reliance on fuel supply chains, according to the research.